2014
DOI: 10.1177/0363546514547226
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis

Abstract: Both ASPBT and OSPBT yield excellent clinical and functional results for the management of isolated superior labrum or long head of the biceps lesions. No significant differences in clinical outcomes as determined by several validated outcome measures were found between the 2 tenodesis methods, nor were any significant range of motion or strength deficits noted at a minimum 2 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 80 publications
2
59
0
2
Order By: Relevance
“…7,11,14,24,27,30 One reason for this school of thought is that younger patients may be more concerned with the cosmesis of a Popeye sign, should it develop. In the current study, 7 tenotomies were performed on the “cosmetically concerned” demographic, age 40 to 49 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,14,24,27,30 One reason for this school of thought is that younger patients may be more concerned with the cosmesis of a Popeye sign, should it develop. In the current study, 7 tenotomies were performed on the “cosmetically concerned” demographic, age 40 to 49 years.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,7,11,16,24 Advantages of tenodesis include closer approximation of the normal muscle-tendon length, which can minimize the Popeye sign (cosmesis) and cramping pain, as well as potentially improved ability to return to physical activity requiring biceps force. 11,14,24,27,28 On the other hand, the downsides of tenodesis include longer healing times, implant costs, postoperative stiffness, persistent pain, and risks of subsequent failure, fracture, and neurovascular injury. 12,19,20,21,28 Selection criteria for each procedure are often driven by a surgeon’s personal algorithm and experience as well as the age, activity level, and desires of the patient.…”
mentioning
confidence: 99%
“…LHB tenodesis can be positioned on the bicipital groove, the “suprapectoral” position below the bicipital groove at the superior border of the pectoralis major tendon, the subpectoral position, or on others such as the conjoint tendon, cuff or soft tissue by means of suture fixation. 14 It can be performed under arthroscopy proximally on the groove but several authors report residual pain from the so-called “hidden lesions,” or pathologic LHB that is left in the gutter unreleased from its sheath, which turn the subpectoral fixation an attractive option. 15 , 16 , 17 Likewise, a subpectoral fixation eliminates any further sawing of the LHB tendon through the rotator cuff tendons.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 Published studies comparing open subpectoral with arthroscopic tenodesis have shown mixed results. 13 , 14 , 15 However, a recent systematic review 3 demonstrated no significant differences when techniques were compared. Even for surgeons who prefer open subpectoral tenodesis, the described technique for identification and exposure of the proximal biceps tendon can still offer potential benefits as it facilitates both visual assessment of the entire course of the biceps and subsequent externalization of the biceps tendon by allowing for release of biceps adhesions within the groove.…”
mentioning
confidence: 99%
“… 11 , 12 Alternatively, an open, subpectoral tenodesis technique can be used. 1 , 2 , 3 , 6 , 13 , 15 Proponents of the open subpectoral technique argue that it eliminates the risk of residual tenosynovitis by completely removing the tendon from the biceps groove. Reported complications using this open subpectoral technique, however, include infection, nerve injury, and fracture.…”
mentioning
confidence: 99%